Failure assessment : comparison of the failure mode between OPC mic and fiber mix concrete slab - Cheng, Kam Hao (2012)
This thesis is consisting about the comparison of failure assessment for OPC reinforced concrete slab and fiber added reinforced concrete slabs. The objectives of this thesis are to determine the ultimate load that can withstand by the slabs, the deflection of the slabs, and the crack pattern caused by punching failure. A total four slab samples with dimension of 1.6m X 0.8m X 0.15m are being constructed. The four samples are added with four different proportions of fiber. The first sample is not added any fiber as a control sample. 1.8kg of fiber per i meter cube of concrete is added into the second slab samples. The third sample has 0.9kg of fiber per meter cube of concrete.The fourth sample has 0.45kg of fiber per meter cube of concrete. Load is applied at the center point of the samples until the samples are experiencing punching failure. The ultimate load and the maximum deflections occur during the ultimate load is measured. At the end of the experiment, mapping of the cracks occur at the bottom and side of the slab samples are carried out. The experimental results showed the amount of fiber added into the slab samples will affect the ultimate load and deflection of the samples. The data was analyzed and the conclusion is drawn that fiber with proportion of 0.9kg per meter cube of concrete contributes the highest ultimate load and the lowest deflection.